Bayesian Space-Time Patterns and Climatic Determinants of Bovine Anaplasmosis - Hanzlicek, Gregg A.; Raghavan, Ram K.; Ganta, Roman R.; Anderson, Gary Allen (My University, 2016)
The space-time pattern and environmental drivers (land cover, climate) of bovine anaplasmosis in the Midwestern state of Kansas was retrospectively evaluated using Bayesian hierarchical spatio-temporal models and publicly available, remotely-sensed environmental covariate information. Cases of bovine anaplasmosis positively diagnosed at Kansas State Veterinary Diagnostic Laboratory (n = 478) between years 2005-2013 were used to construct the models, which included random effects for space, time and space-time interaction effects with defined priors, and fixed-effect covariates selected a priori using an univariate screening procedure. The Bayesian posterior median and 95% credible intervals for the space-time interaction term in the best-fitting covariate model indicated a steady progression of bovine anaplasmosis over time and geographic area in the state. Posterior median estimates and 95% credible intervals derived for covariates in the final covariate model indicated land surface temperature (minimum), relative humidity and diurnal temperature range to be important risk factors for bovine anaplasmosis in the study. The model performance measured using the Area Under the Curve (AUC) value indicated a good performance for the covariate model (>0.7). The relevance of climatological factors for bovine anaplasmosis is discussed.
Citation: Hanzlicek, G. A., Raghavan, R. K., Ganta, R. R., & Anderson, G. A. (2016). Bayesian Space-Time Patterns and Climatic Determinants of Bovine Anaplasmosis. Plos One, 11(3), 13. doi:10.1371/journal.pone.0151924
Keywords: Continental United-States; Lone Star Tick; Borne Diseases; Temperature; Model; Risk